Expression of Myxovirus Resistance A (MxA) Is Associated with Tumor-Infiltrating Lymphocytes in Human Epidermal Growth Factor Receptor 2 (HER2)–Positive Breast Cancers - Lee, So Jeong (Cancer Res Treat, 2017)
PURPOSE: The prognostic significance of tumor-infiltrating lymphocytes (TILs) has been determined in breast cancers. Interferons can affect T-cell activity through direct and indirect mechanisms. Myxovirus resistance A (MxA) is an excellent marker of interferon activity. Here,we evaluated TILs and MxA expression in human epidermal growth factor receptor 2 (HER2)–positive breast cancers. MATERIALS AND METHODS: Ninety cases of hormone receptor (HR)+/HER2+ tumors and 78 cases of HR–/HER2+ tumors were included. The TILs level was assessed using hematoxylin and eosin–stained full face sections, and MxA expressionwas evaluated by immunohistochemistrywith a tissue microarray. RESULTS: MxA protein expression was significantly higher in tumors with high histologic grade (p=0.023) and high levels of TILs (p=0.002). High levels of TILs were correlated with high histological grade (p=0.001), negative lymphovascular invasion (p=0.007), negative lymph node metastasis (p=0.007), absence of HR expression (p < 0.001), abundant tertiary lymphoid structures (TLSs) around ductal carcinoma in situ (p=0.018), and abundant TLSs around the invasive component (p < 0.001). High levels of TILs were also associated with improved disease-free survival, particularly in HR–/HER2+ breast cancers. However, MxA was not a prognostic factor. CONCLUSION: High expression of MxA in tumor cells was associated with high levels of TILs in HER2-positive breast cancers. Additionally, a high level of TILs was a prognostic factor for breast cancer, whereas the level of MxA expression had no prognostic value.